Posterior Reversible Encephalopathy Syndrome Secondary to Hypercalcemia in a Teenager: A Case Report - Valeria Roldan; Catalina Aron-Said; Patricia Bejar; Jose Cotrina; Giancarlo Sante; Hector Sosa; Arturo E. Villena (Annals of Internal Medicine: Clinical Cases)
This case details an atypical presentation of a common clinical condition, primary hyperparathyroidism. A 16-year-old girl with no medical history presented with status epilepticus and hypertension. She reported a 3-month history of asthenia, nausea, vomiting, polyuria, and weight loss, as well as an episode of sudden vision loss with persistent blurriness. Her serum calcium was 3.94 mmol/L and her level of parathyroid hormone was 28.16 pmol/L. T2-weighted magnetic resonance imaging of the brain revealed symmetrical bilateral occipito-parietal hyperintensities. Taken together, the clinical context and radiologic findings in this case suggested a diagnosis of posterior reversible encephalopathy syndrome. Hypercalcemia is a rare cause of posterior reversible encephalopathy syndrome.